Molecular surveillance and phylogenetic traits of Babesia bigemina and Babesia bovis in cattle (Bos taurus) and water buffaloes (Bubalus bubalis) from Colombia (2018)
ABSTRACT: Background: Babesia bigemina and B. bovis are two economically important hemoparasites affecting both cattle and buffaloes involved in dairy and beef production. In Colombia, although some parasitological and serological studies suggest an endemicity of these pathogens in areas under 1000 m, little is known about its molecular prevalence in different host. The objective of this study was to estimate the prevalence and molecular traits of these parasites in cattle and buffaloes from two Colombian regions. Methods: Between 2014 and 2016, a three-point longitudinal survey was designed in farms from Caribbean and Orinoquia regions to evaluate the molecular prevalence of B. bigemina and B. bovis using a nested PCR (n-PCR) targeting hypothetical protein (hyp) and rhoptry-associated protein (RAP-1) genes, respectively. A total of 1432 cattle, 152 buffalo and 1439 Rhipicephalus microplus samples were analyzed. Moreover, phylogenetic relationship of isolates was analyzed using the 18S rRNA gene. Results: A molecular prevalence of 31.6% (24.2% for B. bigemina and 14.4% for B. bovis), 23.6% (6.5% for B. bigemina and 17.7% for B. bovis) and 4.3% (3.5% for B. bigemina and 1.0% for B. bovis) was observed in cattle, buffaloes and Rhipicephalus microplus, respectively. Higher values of infection were observed during the wet season and late wet season; nevertheless, other variables such as age, production type, sex, breed and babesiosis control were also significantly associated with infection. Prevalence analysis showed that B. bovis infection was higher in cattle that coexist with buffaloes, when compared to those which did not. For each species, phylogenetic analyses revealed a high genetic diversity of isolates without clusters related to the isolation source. Conclusions: To our knowledge, this is the first longitudinal survey that evaluates through molecular methods, the infection of B. bigemina and B. bovis in two important livestock regions from Colombia. This study reveals that the prevalence of infection by Babesia spp., in cattle and buffaloes are modulated by seasonal variations, host factors and vector traits. Our results provide new insights on the epidemiological aspects of infection of Babesia spp., in cattle and buffaloes, which must be taken into consideration when babesiosis control programs are implemented in the study area.